- - Dörr Zegers, Otto (Acta Bioethica, 2000)
Suicide can be understood only as a result of a previous reflection about death. With reference to some texts by Hegel, Goethe and Heidegger, the author proposes a conception of death, not only as a part of life but also as ‘that' that gives meaning to it. A similar idea, though expressed in a very original way, is the one sustained by the poet Rainer Maria Rilke in a letter to his editor in Polish, W. Hulewicz, of November 13, 1925. The author tries to study more deeply the poet's thought concerning death, through the analysis of the Eighth, Ninth and Tenth Duino Elegies (1922), poems where Rilke develops his concept of the "personal death", announced in his novel, The notes of Malte Laurids(1910). To him, life itself consists of Brigge "learning to die", of preparing in advance "the masterpiece of a noble death.. ., of a consummate, happy and enthusiastic death, as only saints were able to conceive it". Then, the question is what could happen to induce someone not to wait for his /her own death and destroy with a suicidal act the harmony of life and death?. The poet gives the answer in the Requiem for Wolf von Kalckreuth (1908). The one committing suicide does not recognize in earth the possibility of joy, as something that, sometimes, is hidden amid pain. Secondly, the suicide hurries to give life and death a definitive interpretation, without allowing life -in its own way- to unveil the meaning of the existence. Finally, Rilke's suicidal young, who happened to be a poet, did not let his work mature, perhaps he did not understand what was the essence of poetry: that the poet transforms himself in the words that eternalize things.